2015
DOI: 10.1371/journal.pone.0120470
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Geographic Distribution of gyrA and gyrB Mutations Associated with Fluoroquinolone Resistance in Clinical Mycobacterium Tuberculosis Isolates: A Systematic Review

Abstract: BackgroundThe detection of mutations in the gyrA and gyrB genes in the Mycobacterium tuberculosis genome that have been demonstrated to confer phenotypic resistance to fluoroquinolones is the most promising technology for rapid diagnosis of fluoroquinolone resistance.MethodsIn order to characterize the diversity and frequency of gyrA and gyrB mutations and to describe the global distribution of these mutations, we conducted a systematic review, from May 1996 to April 2013, of all published studies evaluating M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
95
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 67 publications
18
95
4
3
Order By: Relevance
“…The codon 90 mutation A90V has also been found at a high frequency; studies from India, the Philippines, China, and Belgium have reported it as the most common mutation (23,24,35,42). The review by Avalos et al found that A90V accounted for 13 to 20% of mutations contributing to resistance (32). In the present study, D94G and A90V were the most commonly observed mutations.…”
Section: Figsupporting
confidence: 58%
See 1 more Smart Citation
“…The codon 90 mutation A90V has also been found at a high frequency; studies from India, the Philippines, China, and Belgium have reported it as the most common mutation (23,24,35,42). The review by Avalos et al found that A90V accounted for 13 to 20% of mutations contributing to resistance (32). In the present study, D94G and A90V were the most commonly observed mutations.…”
Section: Figsupporting
confidence: 58%
“…In another review, across 18 countries, by Avalos et al, mutation data for 3,846 clinical isolates with known profiles of phenotypic resistance to FQ were studied. The most frequent gyrA mutation was D94G, which ranged from 21 to 32% (32). The relative frequencies of QRDR mutations reported from different regions worldwide are detailed in Table 2.…”
Section: Figmentioning
confidence: 99%
“…However, in our study, the results showed no significant association between ofloxacin resistance and gyrA mutations, and also, kanamycin resistance and rrs mutations. Based on the correlation studies among these primers, genetic and the geographic distances should be evaluated in a future study [14]. Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown specificities of gene mutations in predicting kanamycin [9] [10] [11] and ofloxacin resistance [11] [12] [13] [14]. Many studies have been conducted on genotypic and phenotypic characteristics of drug resistant M. tuberculosis; however, this kind of study is rare in Thailand [15].…”
Section: Xdr-tb Normally Develops From Multi-drug Resistant Tuberculomentioning
confidence: 99%
See 1 more Smart Citation